Treasury Single Account (TSA) and Revolving Funds in Public Institutions - Felix E. Ojong; A. M. Ogaboh Agba; Felix O. Eteng; Gbadebo S. Maruf; Abayomi I. Akintola; E. U. Usung (Yayasan Ahmar Cendekia Indonesia, 2021)
The study assessed the impact of Treasury Single Account (TSA) on revolving funds in public organisations, with particular reference to drug revolving fund in government hospitals in Nigeria. Specifically the study examines the relationship between appropriation control of TSA, cash management of TSA, payment mechanism of TSA and Drug Revolving Fund (DRF) in public hospitals. Survey method was adopted and 1020 questionnaire were administered. Data generated study were presented in tables and simple percentile. Hypotheses were also tested using Pearson Product Moment Correlation Coefficient (PPMC). Findings established significant links between appropriation control of TSA, cash management of TSA, payment mechanism of TSA and DRF in public hospitals. It was recommended among other that management should carryout monthly review of cash management of DRF to ensure that adequate funds are availability for drugs administration in public hospitals.